Graphite carbon nano composite material, porous lithium metal negative electrode material as well as preparation method and application of porous lithium metal negative electrode material
By preparing graphite carbon nanocomposite materials and porous lithium metal negative electrode materials with sandwich structure, the problem of insufficient circulation and affinity of lithium metal negative electrode materials in lithium-ion batteries is solved, the energy density and Coulomb efficiency of lithium batteries are improved, and the battery is extended life.
Patent Information
- Application Number
- CN202411245905.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-17
AI Technical Summary
Lithium metal negative electrode materials have cycling problems in lithium-ion batteries, such as the growth and short circuit of lithium dendrites, resulting in a decrease in capacity and Coulomb efficiency, shortening of life, and insufficient affinity between nano-carbon materials and lithium, limiting its application.
By preparing a graphite carbon nanocomposite with a sandwich structure, the network structure of the carbon nanomaterial and the lithium-philicity of graphite can be used to reduce the lithium ion nucleation overpotential, inhibit the growth of lithium dendrites, and form a lithium metal negative electrode material through the porous structure. Improve its carrier capacity.
It significantly improves the lithium-philicity of lithium ions embedded and removed, extends the life of lithium batteries, improves the energy density and Coulomb efficiency of lithium batteries, reduces the growth of lithium dendrites, and enhances the stability of lithium metal negative electrodes.
Smart Images

Figure BDA0005030718580000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and specifically relates to a graphite-carbon nanocomposite material, a porous lithium metal negative electrode material, and a preparation method and application thereof. Background Art
[0002] Electric vehicles have become a viable alternative to internal combustion engines, offering a solution to reduce environmental pollution and dependence on underground resources. This shift has accelerated the development of high-performance energy storage technologies, with lithium-ion batteries being an example. Exploration efforts to increase the energy density of lithium-ion batteries are still ongoing in different areas, including cathode active materials, solid-state electrolytes, and silicon anode materials. Despite these efforts, graphite with a capacity of 372 mAh / g remains the predominant anode material used in commercial lithium-ion batteries. However, graphite has limited capacity and inherent limitations in meeting the requirements for increased energy density. As an alternative anode material, lithium metal anodes have attracted attention due to their significant specific capacity (3860 mAh / g) and low redox potential (3.04 V relative to standard hydrogen electrode) and have been used in lithium metal batteries.
[0003] However, lithium metal anodes are susceptible to cycling problems, including lithium dendrite growth and short circuit phenomena. These challenges are mainly caused by the uneven deposition and dissolution of lithium ions. In addition, an irreversible reaction occurs between lithium metal and the organic electrolyte to produce a solid electrolyte interface (SEI), which leads to the consumption of active lithium in the electrolyte. Since SEI is usually unable to adapt to the drastic volume expansion during the cycle with lithium metal, the SEI layer tends to crack, thereby depleting the active lithium in the electrolyte, which leads to a continuous decrease in capacity and coulombic efficiency, and a sharp decline in life.
[0004] Therefore, many studies are currently working to overcome the above challenges associated with lithium metal batteries. Using porous structures as the skeleton of lithium metal anodes to form lithium metal composites is expected to be the best solution for lithium metal anodes, but the affinity between nanocarbon materials and lithium is a major obstacle in this direction. Summary of the invention
[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing a graphite carbon nanocomposite material; the second purpose of the present invention is to provide a graphite carbon nanocomposite material prepared by the preparation method; the third purpose of the present invention is to provide a method for preparing a porous lithium metal negative electrode material; the fourth purpose of the present invention is to provide a porous lithium metal negative electrode material prepared by the preparation method; the fifth purpose of the present invention is to provide the application of the porous lithium metal negative electrode material in the preparation of lithium batteries.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a graphite-carbon nanocomposite material, the preparation method comprising the following steps:
[0008] Step 1, adding ferrocene and thiophene to an acetone solution, and mixing them evenly to obtain a precursor solution;
[0009] Step 2, injecting the precursor solution into a vertical tube furnace, heating it at high temperature in a carrier gas atmosphere to react, and obtaining a reactant;
[0010] Step 3, the reactants are cooled and extruded and stretched into a film;
[0011] Step 4, mixing and grinding graphite, an organic solvent, and polyvinylidene fluoride, and stirring to obtain a graphite mixed solution;
[0012] Step 5: Take 2 portions of the membranes prepared in step 3, spray the graphite mixed solution prepared in step 4 on the surface of one of the membranes to form a coating on the membrane surface, cover the coating sprayed with the graphite mixed solution with the other membrane, and heat and cure to obtain a three-layer graphite carbon nanocomposite material with two membranes and one coating layer.
[0013] Single-layer graphite only has lithium affinity and cannot serve as the skeleton of lithium metal negative electrode. It does not have the ability to become the carrier of lithium metal negative electrode and will accelerate the disordered growth of lithium dendrites. The present invention creatively prepares a graphite-carbon nanocomposite material with a sandwich structure through graphite and carbon nanomaterials, improves the inherent extremely poor lithium affinity of carbon nanomaterials, and the lithium affinity of the prepared graphite-carbon nanocomposite material is greatly improved; in addition, the method of the present invention reduces the lithium ion nucleation overpotential by means of the network structure of carbon nanomaterials and the lithium affinity of graphite itself, and effectively inhibits the growth of lithium dendrites.
[0014] In the above-mentioned preparation method, preferably, in step 1, based on the weight of the acetone solution as 100wt%, the amount of ferrocene added is 10-12wt%, and the amount of thiophene added is 7-8wt%. The amount of ferrocene and thiophene used in the present invention is determined through a creative process; if ferrocene is excessive, the nano-carbon material cannot be grown, if thiophene is excessive, the nano-carbon material cannot grow in an orderly manner, and if ferrocene is too little, the grown nano-carbon material agglomerates too much, and if thiophene is too little, the polar groups are few, and the nano-carbon material has weak lithium affinity.
[0015] In the above preparation method, preferably, in step 2, the atmosphere of the carrier gas is selected from hydrogen, helium or argon.
[0016] In the above preparation method, preferably, in step 2, the high temperature heating temperature is 1200°C to 1300°C.
[0017] In the above preparation method, preferably, in step three, the reactants are cooled to a temperature of 45° C. to 60° C. and then extruded and stretched to form a film.
[0018] In the above preparation method, preferably, in step 4, the organic solvent is selected from N-methyl-2-pyrrolidone.
[0019] In the above preparation method, preferably, in step 4, the mass ratio of the graphite, the organic solvent and the polyvinylidene fluoride is (0.8-1.2):(2.8-3.2):(0.1-0.3).
[0020] In the above preparation method, preferably, in step 4, the stirring time is 6 to 12 hours.
[0021] In the above preparation method, preferably, in step 5, the mass ratio of the graphite to the graphite carbon nanocomposite material is 1:12 to 1:10, preferably 1:11. This ratio can ensure that the graphite and the graphite carbon nanocomposite material are matched to obtain a graphite carbon nanocomposite material with good stability and the strongest lithium affinity.
[0022] In the above preparation method, preferably, the temperature of heating and curing is 120° C. to 125° C., and the time is 6 to 8 hours.
[0023] On the other hand, the present invention also provides a graphite-carbon nanocomposite material, which is prepared by the above-mentioned preparation method.
[0024] In another aspect, the present invention further provides a method for preparing a porous lithium metal negative electrode material, the preparation method comprising the following steps:
[0025] The graphite carbon nanocomposite material prepared by the above preparation method or the above graphite carbon nanocomposite material is used as the positive electrode and lithium metal is used as the negative electrode, an electrolyte is added to form an electrolytic cell, and electricity is turned on for a deposition reaction to deposit the lithium in the negative electrode onto the surface of the graphite carbon nanocomposite material to obtain a porous lithium metal negative electrode material.
[0026] In the above preparation method, preferably, the electrolyte is an electrolyte composed of 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 1,3-dioxolane and ethylene glycol dimethyl ether mixed in a volume ratio of 1:1.
[0027] In the above preparation method, preferably, the current used for powering on is 0.1A for 5h.
[0028] On the other hand, the present invention also provides a porous lithium metal negative electrode material, which is prepared by the above-mentioned preparation method.
[0029] In another aspect, the present invention also provides a porous lithium metal negative electrode material prepared by the above preparation method or the use of the above porous lithium metal negative electrode material in the preparation of a lithium battery.
[0030] Beneficial effects of the present invention:
[0031] The present invention creatively prepares a graphite-carbon nanocomposite material with a sandwich structure through graphite and carbon nanomaterials, thereby improving the extremely poor lithium affinity inherent in the carbon nanomaterials, and the lithium affinity of the prepared graphite-carbon nanocomposite material is greatly improved; in addition, the method of the present invention reduces the lithium ion nucleation overpotential by means of the network structure of the carbon nanomaterials and the lithium affinity of the graphite itself, and effectively inhibits the growth of lithium dendrites.
[0032] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail below. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0034] Embodiment 1:
[0035] This embodiment provides a method for preparing a graphite-carbon nanocomposite material, the preparation method comprising the following steps:
[0036] (1) Based on the weight of the acetone solution being 100 wt %, 10 wt % of ferrocene and 7 wt % of thiophene are added to the acetone solution, and the mixture is mixed uniformly to obtain a precursor solution;
[0037] (2) injecting the precursor solution prepared in step (1) into a vertical tube furnace, and heating the solution at 1200° C. in a hydrogen carrier gas atmosphere to obtain a reactant;
[0038] (3) When the reactant obtained in step (2) is cooled to 45° C., it is extruded and stretched into a film, and then wound into a roll for storage;
[0039] (4) mixing and grinding graphite, N-methyl-2-pyrrolidone, and polyvinylidene fluoride in a mass ratio of 1:3:0.2, and stirring evenly at room temperature for 6 hours to obtain a graphite mixed solution;
[0040] (5) Take two portions of the membranes prepared in step (3), spray the graphite mixed solution prepared in step (4) on the surface of one of the membranes to form a coating on the membrane surface, cover the coating sprayed with the graphite mixed solution with another membrane, heat and cure at 120° C. for 6 h, and obtain a three-layer graphite-carbon nanocomposite material with two layers of membranes and one layer of coating; wherein, during the spraying process, the mass ratio of graphite to the finally prepared graphite nanocomposite material is ensured to be 1:11.
[0041] This embodiment also provides a method for preparing a porous lithium metal negative electrode material using the graphite nanocomposite material prepared above. The specific preparation method is as follows:
[0042] The graphite carbon nanocomposite material prepared as above was used as the positive electrode and lithium metal as the negative electrode, an electrolyte (composed of 1 M lithium bistrifluoromethanesulfonyl imide (LiTFSI), 1,3-dioxolane and ethylene glycol dimethyl ether mixed in a volume ratio of 1:1) was added to form an electrolytic cell, and a current of 0.1 A was discharged for 5 h for a deposition reaction to deposit the lithium in the negative electrode onto the surface of the three-layer structure material to obtain a porous lithium metal negative electrode material.
[0043] Comparative Example 1:
[0044] This comparative example provides a method for preparing a graphite carbon nanocomposite material, which comprises the following steps:
[0045] (1) Based on the weight of the acetone solution being 100 wt %, 10 wt % of ferrocene and 7 wt % of thiophene are added to the acetone solution, and the mixture is mixed uniformly to obtain a precursor solution;
[0046] (2) injecting the precursor solution prepared in step (1) into a vertical tube furnace, and heating the solution at 1200° C. in a hydrogen carrier gas atmosphere to obtain a reactant;
[0047] (3) When the reactant obtained in step (2) is cooled to 45° C., it is extruded and stretched into a film, and then wound into a roll for storage;
[0048] (4) mixing and grinding graphite, N-methyl-2-pyrrolidone, and polyvinylidene fluoride in a mass ratio of 1:3:0.2, and stirring evenly at room temperature for 6 hours to obtain a graphite mixed solution;
[0049] (5) Take two portions of the membranes prepared in step (3), spray the graphite mixed solution prepared in step (4) on the surface of one of the membranes to form a coating on the membrane surface, cover the coating sprayed with the graphite mixed solution with another membrane, heat and cure at 120° C. for 6 h, and obtain a three-layer graphite-carbon nanocomposite material with two membranes and one coating layer; wherein, during the spraying process, the mass ratio of graphite to the finally prepared graphite nanocomposite material is ensured to be 11:1.
[0050] Test experiment:
[0051] The porous lithium metal negative electrode material prepared in Example 1 of the present invention and Comparative Example 1 was used as the negative electrode and LiFePO4 as the positive electrode to assemble a button battery; the control group used a lithium sheet as the negative electrode and LiFePO4 as the positive electrode to assemble a button battery, and the battery performance was tested for compatibility with a blue battery at a current of 0.5C; the battery was tested for deposition / stripping at a current of 0.1C. The test results are shown in Table 1 below.
[0052] Table 1
[0053]
[0054] It can be seen from the experimental results in Table 1 that the overpotential of the porous lithium metal negative electrode is lower, which is more conducive to nucleation and uniform deposition of lithium ions. The compatibility test results show that the capacity released by the porous lithium metal negative electrode material is higher, mainly because its composite structure has better lithium affinity, which is conducive to the insertion and extraction of lithium ions and the capacity of the positive electrode material. In addition, with excessive graphite, the deposited lithium ions cannot be delayed and have no capacity. The performance compatibility test is only 35mAhg -1 .
[0055] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a graphite-carbon nanocomposite material, characterized in that: The preparation method comprises the following steps: Step 1, adding ferrocene and thiophene to an acetone solution, and mixing them evenly to obtain a precursor solution; Step 2, injecting the precursor solution into a vertical tube furnace, heating it at high temperature in a carrier gas atmosphere to react, and obtaining a reactant; Step 3, the reactants are cooled and extruded and stretched into a film; Step 4, mixing and grinding graphite, an organic solvent, and polyvinylidene fluoride, and stirring to obtain a graphite mixed solution; Step 5: Take 2 portions of the membranes prepared in step 3, spray the graphite mixed solution prepared in step 4 on the surface of one of the membranes to form a coating on the membrane surface, cover the coating sprayed with the graphite mixed solution with the other membrane, and heat and cure to obtain a three-layer graphite carbon nanocomposite material with two membranes and one coating layer.
2. The preparation method according to claim 1, characterized in that: In step 1, based on 100 wt% of the weight of the acetone solution, the amount of ferrocene added is 10-12 wt%, and the amount of thiophene added is 7-8 wt%.
3. The preparation method according to claim 1, characterized in that: In step 2, the atmosphere of the carrier gas is selected from hydrogen, helium or argon; Preferably, in step 2, the high temperature heating temperature is 1200°C to 1300°C.
4. The preparation method according to claim 1, characterized in that: In step three, the reactants are cooled to a temperature of 45°C to 60°C and then extruded and stretched to form a film.
5. The preparation method according to claim 1, characterized in that: In step 4, the organic solvent is selected from N-methyl-2-pyrrolidone; Preferably, in step 4, the mass ratio of the graphite, the organic solvent and the polyvinylidene fluoride is (0.8-1.2):(2.8-3.2):(0.1-0.3); Preferably, in step 4, the stirring time is 6 to 12 hours.
6. The preparation method according to claim 1, characterized in that: In step 5, the mass ratio of the graphite to the graphite-carbon nanocomposite material is 1:12 to 1:10, preferably 1:11; Preferably, the temperature of the heating curing is 120° C. to 125° C., and the time is 6 to 8 hours.
7. A graphite-carbon nanocomposite material prepared by the preparation method according to any one of claims 1 to 6.
8. A method for preparing a porous lithium metal negative electrode material, characterized in that: The preparation method comprises the following steps: The graphite carbon nanocomposite prepared by the preparation method according to any one of claims 1 to 5 or the graphite carbon nanocomposite according to claim 7 is used as the positive electrode and lithium metal is used as the negative electrode, an electrolyte is added to form an electrolytic cell, and a deposition reaction is carried out by powering on to deposit the lithium in the negative electrode onto the surface of the graphite carbon nanocomposite to obtain a porous lithium metal negative electrode material; Preferably, the electrolyte is an electrolyte composed of 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1; Preferably, the current used for powering on is 0.1A for discharging for 5 hours.
9. A porous lithium metal negative electrode material, which is prepared by the preparation method according to claim 8.
10. Use of the porous lithium metal negative electrode material prepared by the preparation method according to claim 8 or the porous lithium metal negative electrode material according to claim 9 in the preparation of lithium batteries.
